Contemporary Sport Management - Pedersen, Paul M. (Human Kinetics, 2025)
Contemporary Sport Management is a comprehensive introduction to the profession. This textbook broadens students' understanding of sport management issues, emphasizing critical thinking, ethics, and diversity while providing students with an introduction to all the aspects of the field they need to know as they prepare to enter the profession.